Generation of path-polarization hyperentanglement using quasi-phase-matching in quasi-periodic nonlinear photonic crystal - Guangqiang He (Nature Portfolio, 2017)
Abstract A compact scheme for the generation of path-polarization entangled photon pairs is proposed by using a quasi-periodic nonlinear photonic crystal to simultaneously accomplish four spontaneous parametric down-conversion processes. Moreover, we report experimental scheme to measure the polarization entanglement and path entanglement separately and theoretically get numerical results that verify some predictions about the hyperentanglement. This method can be expanded for the generation of multi-partite and two-photon path-polarization hyperentanglement in a single quasi-periodic nonlinear photonic crystal structure. This compact quantum light source can be used as a significant ingredient in quantum information science.